Algorithms and Applications ALAP 2018 (Smart Innovation, Systems and Technologies,, 2018)
This book presents the proceedings of the Conference on Algorithms and Applications (ALAP 2018), which focuses on various areas of computing, like distributed systems and security, big data and analytics and very-large-scale integration (VLSI) design. The book provides solutions to a broad class of problems in diverse areas of algorithms in our daily lives in a world designed for, and increasingly controlled by algorithms. Written by eminent personalities from academia and industry, the papers included offer insights from a number of perspectives, providing an overview of the state of the art in the field. The book consists of invited talks by respected speakers, papers presented in technical sessions, and tutorials to offer ideas, results, work-in-progress and experiences of various algorithmic aspects of computational science and engineering.